2006
DOI: 10.4049/jimmunol.177.12.8822
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the B Cell Epitopes Associated with a Truncated Form of Pseudomonas Exotoxin (PE38) Used to Make Immunotoxins for the Treatment of Cancer Patients

Abstract: Recombinant immunotoxins composed of an Ab Fv fragment joined to a truncated portion of Pseudomonas exotoxin A (termed PE38) have been evaluated in clinical trials for the treatment of various human cancers. Immunotoxin therapy is very effective in hairy cell leukemia and also has activity in other hemological malignancies; however, a neutralizing Ab response to PE38 in patients with solid tumors prevents repeated treatments to maximize the benefit. In this study, we analyze the murine Ab response as a model t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
129
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(129 citation statements)
references
References 80 publications
0
129
0
Order By: Relevance
“…We are unable to test the immunogenicity of HA22-LR-LO10 in humans so instead we assessed its antigenicity; that is, the binding of HA22-LR-LO10 to preexisting antibodies made against native RIT, as a surrogate measure of the immune response (9). We previously showed in mice that immunogenicity and antigenicity are closely related (13). We performed a competition assay in which we measured the concentration of RIT that reduced the level of patient serum antibodies reacting with HA22 by 50% (18).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We are unable to test the immunogenicity of HA22-LR-LO10 in humans so instead we assessed its antigenicity; that is, the binding of HA22-LR-LO10 to preexisting antibodies made against native RIT, as a surrogate measure of the immune response (9). We previously showed in mice that immunogenicity and antigenicity are closely related (13). We performed a competition assay in which we measured the concentration of RIT that reduced the level of patient serum antibodies reacting with HA22 by 50% (18).…”
Section: Resultsmentioning
confidence: 99%
“…1). Both domains II and III contain B-cell epitopes (13). The B-cell epitopes in domain II were removed when we found that all of domain II, except for the furin-processing site, could be excised without greatly diminishing the cytotoxic activity of the RIT (17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations